ANALYSIS OF THE ROLE OF TEACHERS IN BUILDING EARLY CHILDHOOD DISCIPLINE CHARACTER THROUGH BEHAVIOR CONTRACT TECHNIQUES IN PRESCHOOLS THROUGHOUT KALIBUNDER SUB-DISTRICT - Suminar, Dedeh; Elnawati, Elnawati; Munajat, Asep (Penerbit Lafadz Jaya, 2024)
One of the most important factors that can improve the character of children's discipline is to perform behavior contract techniques on children. The purpose of this study is to determine the role of teachers in building disciplinary character through behavior contract techniques. The data of this study are all ECCE teachers who have applied behavior contract techniques, with a sample of 100 people. The method used in this study is descriptive with a quantitative approach. The method of data collection in this study is the distribution of questionnaires in the form of questions to respondents. Simple linear regression analysis was used as an analysis method in this study. The results explained that the character of discipline had a significant effect on behavior contract techniques, and the effect was 65.2% while 34.8% was influenced by other variables.